Leaf Stable Isotope and Nutrient Status of Temperate Mangroves As Ecological Indicators to Assess Anthropogenic Activity and Recovery from Eutrophication - Gritcan, Iana; Duxbury, Mark; Leuzinger, Sebastian; Alfaro, Andrea C. (Frontiers in Plant Science, 2016)
We measured nitrogen stable isotope values (δ15N), and total phosphorus (%P) and total nitrogen (%N) contents in leaves of the temperate mangrove (Avicennia marina sp. australasica) from three coastal ecosystems exposed to various levels of human impact (Manukau, high; Mangawhai, low; and Waitemata, intermediate) in northern New Zealand. We measured δ15N values around 10‰ in environments where the major terrestrial water inputs are sewage. The highest average total nitrogen contents and δ15N values were found in the Auckland city region (Manukau Harbour) at 2.2%N and 9.9‰, respectively. The lowest values were found in Mangawhai Harbour, situated about 80 km north of Auckland city, at 2.0%N and 5.2‰, respectively. In the Waitemata Harbour, also located in Auckland city but with less exposure to human derived sewage inputs, both parameters were intermediate, at 2.1%N and 6.4‰.Total phosphorus contents did not vary significantly. Additionally, analysis of historical mangrove leaf herbarium samples obtained from the Auckland War Memorial Museum indicated that a reduction in both leaf total nitrogen and δ15N content has occurred over the past 100 years in Auckland’s harbours. Collectively, these results suggest that anthropogenically derived nitrogen has had a significant impact on mangrove nutrient status in Auckland harbours over the last 100 years. The observed decrease in nitrogenous nutrients probably occurred due to sewage system improvements. We suggest that mangrove plant physiological response to nutrient excess could be used as an indicator of long-term eutrophication trends. Monitoring leaf nutrient status in mangroves can be used to assess environmental stress (sewage, eutrophication) on coastal ecosystems heavily impacted by human activities. Moreover, nitrogen and phosphorus leaf contents can be used to assess levels of available nutrients in the surrounding environments.